PENGARUH KELENGKAPAN PRODUK HUKUM KEUANGAN PUBLIK TERHADAP PARTISIPASI PUBLIK DI JARINGAN DOKUMENTASI INFORMASI HUKUM (JDIH) DPRD KOTA BANDUNG - Ilfani, Binta Sekarlia; Firmansyah, Anry (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the effect of the completeness of public financial legal documents in the JDIH of the Bandung City DPRD on public participation by applying the DeLone and McLean model. The research employed a quantitative approach involving 110 respondents and was analyzed using SEM-PLS. The results indicate that service quality and net benefits have a positive and significant effect on public participation, while system quality and information quality have a negative and significant effect. Use and user satisfaction do not have a significant effect. The model demonstrates moderate explanatory power (R² = 0.582). These findings confirm that public participation is more strongly influenced by perceived tangible benefits and the quality of service interaction than by the technical aspects of the system.